Breaking and building the wall: the biology of the blood-brain barrier in health and disease (Swiss Medical Weekly, 2013)
The blood-brain barrier (BBB) is a complex feature of brain endothelial cells that restricts the passage of blood-borne molecules into the brain parenchyma, while ensuring the delivery of essential nutrients and selected biomolecules. Brain vasculature is anatomically distinct from that of other organs and comprises in addition to endothelial cells, pericytes and astrocytes, which collectively form the neurovascular unit (NVU). This review focuses on the regulation of BBB properties by the NVU and the periphery. A brief overview of cellular components of the NVU, and BBB characteristics will be provided, with more emphasis placed on the molecular mechanisms involved in the development of brain vasculature and human genetic diseases primarily affected by dysfunction of components of the NVU. In addition, the regulation of brain vasculature by peripheral factors such as diet and systemic disease is discussed.